Measuring progress toward the Malabo Declaration goals in the midst of COVID-19: A measurement approach for a health systems-sensitive resilience score - Constas, Mark A.; Wohlgemuth, Max; Ulimwengu, John M. (AKADEMIYA2063, 2021)
As an outgrowth of the Comprehensive Africa Agriculture Development Programme (CAADP), the Malabo Declaration on Accelerated Agricultural Growth and Transformation for Shared Prosperity and Improved Livelihoods (AUC 2014) established both a clear strategic direction and a well-articulated set of agriculture-focused strategic priorities for Africa. Beyond the two overarching commitments to supporting the CAADP process and enhancing investments, the Malabo Declaration drew attention to the goals of achieving zero hunger, halving poverty, boosting intra-African trade in agricultural commodities and services, enhancing the resilience of livelihoods and production systems to climate variability and other shocks, and building mutual accountability to actions and results. With climate change pressures, much of the work on resilience, in connection with the Malabo Declaration and other initiatives, is justifiably based in weather-related shocks. The protracted and pervasive effects of a global pandemic have, however, altered the range of risks to which resilience may be viewed as a strategic response. The present chapter is therefore motivated by the need to explore how indicators related to the shocks and stresses caused by COVID-19 may be incorporated into the CAADP measurement process.